PREPARATION OF CARBON SUPPORTED NICKEL CATALYST AND ITS ADSORPTION BEHAVIOUR FOR COPPER FROM AQUEOUS SOLUTIONS - Yamin, T.; Ansari, M. S.; Ahmed, R.; Chaudhary, M. M. (The Nucleus, 2020)
Nickel catalysts have numerous industrial applications in hydrocarbon chemistry, hydrogenation of oil, fuel cells and many other areas. Addition of nickel to platinum supported on carbon increases the catalytic activity of platinum significantly for fuel cells. Graphite carbon of 100-mesh size was used for the preparation of nickel catalyst. Graphite was given acid treatments and dried. Nickel solution was added under an inert atmosphere, heated at 200o C and dried under vacuum at 100o C overweight. Method for the preparation of the catalyst is described. Copper is an pollutant and is also used in catalysts. Its adsorption on catalyst can be used for the evaluation of catalytic activity of catalyst and also for removal purposes. Adsorption behaviour of copper on the nickel catalysts was studied, Effect of pH, shaking time, loading capacity and adsorbent weight was investigated. The data was tested for Langmuir, Freundlich and Dubinin– Radushkevich adsorption isotherms. The monolayer sorption capacity and adsorption constant related to the Langmuir isotherm are (65±2)x10-5 mol g-1 and (12.3 ±0.6)x 104 L. mol –1 . The Freundlich constant 1/n and Cm are found to be 0.32±0.2 and 0.12 ±0.02 mmol g-1 respectively. The mean free energy of copper adsorption on catalyst is 14.7 ± 0.3 kJ mol –1 which indicates chemical sorption. The effect of temperature was studied and thermodynamic parameters ΔH, ΔS and ΔG were evaluated and found to be 34 ± 1 kJ mol –1, 123 ± 3 J mol –1 K –1 and –2.7 ± 0.1 kJ mol –1 for the adsorption of copper on nickel catalyst. The positive values of enthalpy (ΔH) and entropy (ΔS) and negative value of Gibbs free energy (ΔG) indicate the endothermic, entropy driven and spontaneous nature of sorption. Coating of nickel on graphite increases its catalytic activity significantly.